Procampylaspis australiensis Petrescu 2006, sp. nov. ... - Petrescu, Iorgu (Zenodo, 2006)
Procampylaspis australiensis sp. nov. Figures 42–44 Material examined. Holotype female, NSW, off Nowra, 34°59.52'S, 151°05.94'E, 204m, coarse shell, WHOI epibenthic sled, G.C.B. Poore et al., RV Franklin, 14 Jul 1986 (stn SLOPE 1), NMV J53000. Paratypes: 1 immature male, 1 female (stn SLOPE 45), NMV J53001; 1 female, dissected (stn SLOPE 1), NMV J53002. Diagnosis. Carapace large, with smooth integument.Maxilliped 2 with 6 dactylar teeth. Merus of pereopod 1 as long as carpus, shorter than propodus. Pereopod 2 with short and bulky articles, dactylus twice as long as propodus. Uropod peduncle 1.4 times as long as pleonite 6, 1.1 times as long as its endopod, endopod with 3 inner setae, little longer than exopod. Description of female. Body with smooth integument. Length: 2.6 mm. Carapace 0.46 body length, 1.6 times as long as high, with middorsal ridge, short ocular lobe devoid of lenses, pseudorostral lobes 3 times as long as tip of ocular lobe, antennal notch small, ventral margin smooth. Antenna 1 peduncle ... : Published as part of Petrescu, Iorgu, 2006, Nannastacidae (Crustacea: Cumacea) from eastern Bass Strait, the south-eastern Australian slope, and Antarctica in the collections of Museum Victoria, pp. 129-173 in Memoirs of Museum Victoria 63 (2) on pages 156-158, DOI: 10.24199/j.mmv.2006.63.14, http://zenodo.org/record/10665606 ...